Spontaneous Retroperitoneal Hematoma: A Rare Presentation of Polyarteritis Nodosa - Asad Ullah MD; Asghar Marwat MD; Krithika Suresh MD; Ahmed Khalil MD; Saba Waseem MD, FACP (SAGE Publishing, 2019)
Spontaneous retroperitoneal hematoma is a rare clinical entity that is most commonly caused by renal tumors and vascular disease. In this article, we present a case of spontaneous retroperitoneal hemorrhage caused by polyarteritis nodosa in a patient who presented with severe left flank pain. He underwent computed tomography angiography of his abdomen that showed left retroperitoneal hematoma, which was followed by arteriogram that showed multiple bilateral renal artery aneurysms with active extravasation, findings consistent with polyarteritis nodosa. The patient underwent successful coiling of the bleeding vessel that secured the bleeding and was started on high-dose prednisone, which resulted in resolution of his symptoms.